Psychosocial Advances in Neuro-Oncology - Tamara Ownsworth (Frontiers Research Topics, 2016)
Neuro-oncology is a rapidly growing field concerned with scientific developments and clinical applications related to neuroscience, neuropsychology, cancer and oncology. Neuro-oncological disorders include cancers that directly affect the central nervous system (CNS), such as brain tumours and brain metastases, and non-CNS cancers with treatments that produce neurocognitive impairment. To date, the biological mechanisms and neuropsychological effects of brain tumour and cancer have been the dominant focus in neuro-oncology literature. In terms of psychosocial aspects of care, people's understanding of their diagnosis and symptoms and how they cope with their illness has a major influence on their emotional well-being and quality of life.The development and evaluation of psychological and supportive care interventions for people with brain tumour is an area of emerging research and of high interest to health professionals working in the field. This Research Topic aims to enhance understanding of the psychological and social consequences of brain tumour and other cancers impacting neurocognitive function. It also aims to showcase new developments in assessment and psychosocial intervention approaches.